DECRYPT trial: study protocol for a phase II randomised controlled trial of cognitive therapy for post-traumatic stress disorder (PTSD) in youth exposed to multiple traumatic stressors. Issue 7 (1st July 2021) - Allen, Leila; Ashford, Polly-Anna; Beeson, Ella; Byford, Sarah; Chow, Jessica; Dalgleish, Tim; Danese, Andrea; Finn, Jack; Goodall, Ben; Grainger, Lauren; Hammond, Matthew; Humphrey, Ayla; et al.
Abstract : Background: Post-traumatic stress disorder (PTSD) is a distressing and disabling condition that affects significant numbers of children and adolescents. Youth exposed to multiple traumas (eg, abuse, domestic violence) are at particular risk of developing PTSD. Cognitive therapy for PTSD (CT-PTSD), derived from adult work, is a theoretically informed, disorder-specific form of trauma-focused cognitive–behavioural therapy. While efficacious for child and adolescent single-event trauma samples, its effectiveness in routine settings with more complex, multiple trauma-exposed youth has not been established. The Delivery of Cognitive Therapy for Young People after Trauma randomised controlled trial (RCT) examines the effectiveness of CT-PTSD for treating PTSD following multiple trauma exposure in children and young people in comparison with treatment as usual (TAU). Methods/design: This protocol describes a two-arm, patient-level, single blind, superiority RCT comparing CT-PTSD (n=60) with TAU (n=60) in children and young people aged 8–17 years with a diagnosis of PTSD following multiple trauma exposure. The primary outcome is PTSD severity assessed using the Children's Revised Impact of Event Scale (8-item version) at post-treatment (ie, approximately 5 months post-randomisation). Secondary outcomes include structured interview assessment for PTSD, complex PTSD symptoms, depression and anxiety, overall functioning and parent-rated mental health. Mid-treatment and 11-month and 29-month post-randomisation assessments will also be completed. Process–outcome evaluation will consider which mechanisms underpin or moderate recovery. Qualitative interviews with the young people, their families and their therapists will be undertaken. Cost-effectiveness of CT-PTSD relative to TAU will be also be assessed. Ethics and dissemination: This trial protocol has been approved by a UK Health Research Authority Research Ethics Committee (East of England–Cambridge South, 16/EE/0233). Findings will be disseminated broadly via peer-reviewed empirical journal articles, conference presentations and clinical workshops. Trial registration: ISRCTN12077707 . Registered 24 October 2016 (http://www.isrctn.com/ISRCTN12077707 ). Trial recruitment commenced on 1 February 2017. It is anticipated that recruitment will continue until June 2021, with 11-month assessments being concluded in May 2022.